Mapping the Increased Protein Digestibility Trait in the High‐Lysine Sorghum Mutant P721Q. Issue 5 (1st September 2016) - Massafaro, Moriah; Thompson, Addie; Tuinstra, Mitch; Dilkes, Brian; Weil, Clifford F.
Abstract : Sorghum [ Sorghum bicolor (L.) Moench] is a dietary staple for >500 million people in over 30 countries of the semiarid tropics. Unlike other major cereals, proteins in sorghum grain become much less digestible after wet cooking. P721Q is a high‐lysine sorghum mutant that exhibits a three‐ to fourfold increase in protein digestibility after cooking as compared with other sorghum cultivars. While its increased lysine content has been traced to decreased levels of a kafirin storage protein, the goal of this study was to identify the genetic determinant of the increased digestibility. Genome sequencing of bulked segregants from a P721Q × BTx623 mapping population revealed the highly digestible protein trait maps to the same cluster of kafirin genes that contain the high‐lysine mutation.